ANALISIS PERENCANAAN PENGADAAN KOMPONEN REM PESAWAT B737-800 NG BERDASARKAN SATUAN CYCLE DAN FLIGHT HOURS DI PT ABC - Komarudin Komarudin; Djoko Suprijatmono Suprijatmono (Bina Teknika, 2020)
As one of the MRO (Maintenance, Repair, Overhaul) company PT ABC had the significant problems in the last 3 years, including concerns regarding the difficulty of determining the amount of material availability and timing of procurement the material appropriate to support maintenance activities. In this case the components studied are two type brake of aircraft the first one is brake assembly and the second one is brake Goodrich which installed on B737-800 aircraft NG. Based on historical data, in last 3 years PT ABC have a number of component shortage that continues to grow, in last year PT ABC had 12 unit shortage component for brake assembly and 13 unit shortage component for brake goodrich. It is gave the negative impact for company and also customer PT ABC. To overcome these problems need to be analyzed how to determine the accuracy the number of brake requests that will removal in future periods which resulting the accuracy of the flight time (dispatch reliability/delay time).The proccess in this reserach first determine the life time of brake, determine the quantity of removal brake, schedule of removal brake, account the forecast of requirement brake in next years and determine the planning of material requirement for maintenance proccess. The forecasting using single exponential smoothing methode to determine forecasting result of brake requirement in 2017. This methode consider the smallest standar error estimate of forecasting demand to get the exact result. Morever MRP (material requirement planning) methode used to determine the procurement components planning (Petition Requirement Planning) with forecasting data from previous year's demand. Based on studies result showed that the quantity of brake assembly and brake Goodrich types that should be available for the removal of as many as 13 units per each type of brake for a period in 2017, while the limit (age component) of brake assembly 38 days and 41 days for brake Goodrich and the estimation schedule of brake removal is the last date installation brake plus the actual age of brake that has determined the schedule of brake assembly in 21st of the months 12 and the 2nd of the month 11 for brake Goodrich and result are showed that MRP decrease the shortage of brake assembly 1 unit and decrease the shortage of brake goodrich 2 unit.